Correlation between Voltage Concepts and Daily Life Activities Using POE2WE Model as Character Education Reinforcement - Rhifa Diana; Ayu Amelia Aprilia; Afiif Curnitasari; Nana Nana (Jurnal Pendidikan Fisika, 2020)
The purpose of this study is to connect the concept of stress formulas in everyday life as a reinforcement of character education in students. This study uses a qualitative approach in the form of descriptive theoretical data with library study techniques. This study also uses the POE2WE model (Prediction, Observation, Explanation, Elaboration, Write, Evaluation). As a method of learning to strengthen character education, it places more emphasis on elaboration to strengthen the character education of student. The results of this study indicate that the concept of stress in physics can be used as a reinforcement of character education for students.